The Implementation of the Teaching at the Right Level (TaRL) Approach to Improve Mathematical Problem-Solving Skills of Third Grade Students - Pamuji, Slamet; Suryani, Suryani; Anggoro, Subuh (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to improve the mathematical problem-solving ability of third-grade elementary school students through the implementation of the Teaching at the Right Level (TaRL) approach. This research was conducted as Classroom Action Research (CAR) over two cycles during the second semester of the 2024/2025 academic year. The study was carried out collaboratively between a classroom teacher and university supervisor to design, implement, and evaluate the learning process. The subjects were third-grade elementary students with varying levels of understanding in basic mathematical concepts, particularly in arithmetic and simple problem solving. Instruments used in the study included teacher and student observation sheets, student worksheets (LKPD), lesson plans (RPP), and pre- and post-tests to measure student abilities. The TaRL approach was implemented by grouping students according to their level of understanding and providing appropriate materials and activities for each level. This strategy ensured that students were not forced to follow lessons that were too difficult or too easy for them. Data analysis was conducted using narrative description for qualitative data and descriptive statistics for quantitative data. The results showed a significant increase in students’ ability to solve mathematical problems. The average score in the pre-test was 28.56, which increased to 81.80 by the end of cycle II. This indicates that the TaRL approach is highly effective in helping third-grade students better understand and confidently engage with mathematical material. It can be concluded that the Teaching at the Right Level (TaRL) approach is a suitable solution for addressing learning gaps in lower grades and can create a more enjoyable and ability-appropriate learning environment for each child.